Enhancing machine learning models with audio augmentation techniques - Pirko, A. I.; Boretska, I. B. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
This paper investigates how audio augmentation techniques improve the classification accuracy of guitar chords. By applying methods such as noise addition, speed modification, and time shifting, a CNN trained on an augmented dataset achieved better results compared to non-augmented data. The findings highlight the importance of task-specific augmentation techniques in enhancing audio analysis